Komunikasi Krisis di MECnesia dan Upaya Pemulihan Citra Perusahaan di Masa Pandemi - Dian Muhtadiah; Hafied Cangara (Journal of Communication Sciences (JCoS), 2022)
The Covid-19 pandemic has impacted the stability of companies in Indonesia, including that experienced by MECNesia. Due to the absence of company income for one year, this company experienced crisis communication so that many employees resigned. This research uses Situational Crisis Communication Theory (SCCT) with qualitative research methods. The results showed that company leaders took a number of strategic steps to overcome crisis communication problems in their companies, including conducting open dialogue with employees, changing the leaner organizational structure, implementing online learning systems, launching for re-branding the company name by inviting journalists and utilizing social media to make public apologies.